The hidden costs of R&D collaboration - Sara Amoroso (European Commission, Joint Research Centre (JRC), 2014)
The paper investigates the barriers to collaboration in terms of hidden transaction costs, by deriving the distribution of the operating costs and sunk costs associated with firms' investment choices in R&D and innovation activities with or without a research partner. To retrieve both fixed and sunk costs of R&D and innovation activities with or without a research partner, we develop and estimate a structural dynamic monopoly model to quantify the linkages between R&D spending, innovation and cooperation investment choices, and endogenous productivity. We find that the sunk costs of innovations are smaller when collaborating with a research partner; the probability to spend in R&D or to innovate increases with the level of productivity, when collaborating in R&D and innovation; finally, we find that the sunk costs of innovation are 1.5 to 3 times smaller than the sunk costs of R&D. Additionally, the suggested structural framework of firm heterogeneity in cost functions offers a straightforward extension to policy impact evaluation.
Keywords: D22; D23; L14; L60; O32; 330; R&D cooperation; transaction costs; dynamic structural model.